Geological conditions affecting the purity of water - Ames, Frank Weber (My University, 1894)
Introduction: The subject of health, its preservation and its restoration, is one that in all civilized communities today demands the attention of many of our clearest and ablest thinkers. Investigating the causes, the cures, and the preventatives of disease we find scores of our brightest intellects zealously laboring for the advancement of science and the welfare of humanity. One of the most important and essential of human wants is water and it forms the subject of one of the principle branches of investigation demanding the scientists attention. Man cannot live without water to drink any more than a tree or plant can live without water in its tissues. It is as necessary for the healthy and harmonious action of his bodily functions as it is for the proper assimilation of mineral foods in vegetable organisms, or the digestion of organic foods in the animal kingdom. A thorough study of its physiological uses reveals its great importance as an agent in building up organic tissues as well as one for tearing own and carrying off waste products and it impresses the investigator with the absolute necessity of using such water as is free from all injurious ingredients.
Citation: Ames, Frank Weber. Geological conditions affecting the purity of water. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Geology; Water; Survival; Biology; Chemistry; Theses; Manuscripts (documents)